2006
DOI: 10.1128/jb.188.3.1169-1174.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Bacteroides Conjugative Transposon, CTnERL, Can Transfer a Portion of Itself by Conjugation without Excising from the Chromosome

Abstract: CTnERL, a Bacteroides conjugative transposon, transferred DNA by an Hfr-type mechanism during conjugation when it was excision deficient due to an insertion in the integrase gene. Rescue of the conjugative transposon sequences required the recipient to be RecA proficient and to contain an integrated CTnERL. The transfer efficiency was only 10-to 30-fold lower than the normal element transfer efficiency, and the direction of transfer from the oriT gene showed that the integrase end was transferred first and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…However, a recent study characterizing the Mob proteins on the CTn341 CTnDOT-related element suggested that the oriT of CTn341 was just upstream of mobA. The previous studies that localized the CTnDOT oriT used subcloned regions in trans to another element, CTnERL, which is also considered to be virtually identical to CTnDOT with the exception that CTnERL lacks the 13-kb ermF region (17,21). Collectively, these observations prompted us to re-evaluate the location of the oriT regions on CTnDOT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study characterizing the Mob proteins on the CTn341 CTnDOT-related element suggested that the oriT of CTn341 was just upstream of mobA. The previous studies that localized the CTnDOT oriT used subcloned regions in trans to another element, CTnERL, which is also considered to be virtually identical to CTnDOT with the exception that CTnERL lacks the 13-kb ermF region (17,21). Collectively, these observations prompted us to re-evaluate the location of the oriT regions on CTnDOT.…”
Section: Resultsmentioning
confidence: 99%
“…4B). Despite the difference in mob transcription results, the two elements are reported to transfer at similar rates, suggesting that the level of mob expression does not directly affect the frequency of conjugative transfer (21,22).…”
Section: Figmentioning
confidence: 99%
“…The two smallest regions sufficient for mobilization overlapped by 267 bp, and this region was termed the putative oriT. However, when the 267-bp region was cloned onto a plasmid, it was not mobilizable (19,48). We did not specifically test this site in CTn341, but it is possible that there is more than one oriT on these large elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of CTns in members of the genera Bacteroides and Vibrio have indicated that the integrase (int), DNA excision protein (exc) and recA genes are involved in CTn excision (Sutanto et al, 2004;Waldor et al, 1996;Whittle et al, 2002bWhittle et al, , 2006. The Bacteroides CTns CTn341 and CTnDOT require exc for their excision (Bacic et al, 2005;Sutanto et al, 2002).…”
Section: Int-dependent Excision Of Ctnpg1mentioning
confidence: 99%